2011
DOI: 10.1128/aac.05133-11
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of Primaquine-Artemisinin Hybrids as a Multistage Antimalarial Strategy

Abstract: It is widely accepted that the struggle against malaria depends on the development of new strategies to fight infection. The "magic bullet" thought to be necessary to reach eradication should not only provide treatment for all Plasmodium spp. that infect human red blood cells but should also eliminate the replicative and dormant liver forms of the parasite. Moreover, these goals should ideally be achieved by using different mechanisms of action so as to avoid the development of resistance. To that end, two hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 40 publications
1
46
0
1
Order By: Relevance
“…Also, in addition to all the properties of trioxane-containing molecules, the hybrid was also able to inhibit the polymerization of ␤-hematin, a property of chloroquine. Similar results have been obtained in the case of artemisinin-primaquine phosphate (artemisininPrimaquine [PQ]) and stilbene-chalcone (30,31) hybrids.…”
Section: Advantages Of Hybridssupporting
confidence: 80%
See 1 more Smart Citation
“…Also, in addition to all the properties of trioxane-containing molecules, the hybrid was also able to inhibit the polymerization of ␤-hematin, a property of chloroquine. Similar results have been obtained in the case of artemisinin-primaquine phosphate (artemisininPrimaquine [PQ]) and stilbene-chalcone (30,31) hybrids.…”
Section: Advantages Of Hybridssupporting
confidence: 80%
“…But to ensure malaria eradication, new drugs are urgently needed that restrict transmission of the parasite between the human host and the mosquito vector and that eliminate the parasite in its various stages during its cycle in the human body. The first study based on the covalent combination of molecules acting on different stages of the parasite life cycle was conducted by Capela et al (30). The work describes the synthesis of hybrid molecules containing PQ and artemisinin (ART) pharmacophoric units, and their efficacies against Plasmodium hepatic and erythrocytic stages, both in vitro and in animal models of malaria.…”
Section: Advantages Of Hybridsmentioning
confidence: 99%
“…This is consistent with what has been previously reported for compounds 3 and 17. 23 Additionally, none of the compounds significantly affected Huh7 cell proliferation, indicating that tetraoxane−PQ hybrids are selective and nontoxic antimalarial agents (Table 1).…”
mentioning
confidence: 99%
“…Screening against P. berghei liver stage of infection revealed that both the tetraoxane-and trioxane-based series are potent inhibitors of the exoerythrocytic forms of the parasite, with IC 50 values in the submicromolar range, being superior to a 1:1 PQ−ART mixture. 23 In vivo studies revealed that compound 5 irreversibly cleared the parasitemia from infected mice, while screening of transmission-blocking activity showed that the tetraoxanes show potent activity in reducing the percentage of infected mosquitoes and the mean number of oocysts per mosquito. These results indicate that these hybrids are excellent starting points to develop agents with the potential to be used in malaria eradication campaigns since they display all the desired antimalarial multistage activities.…”
mentioning
confidence: 99%
“…The presence of more than one structurally active moiety in a single molecule may show an enhanced activity 21 . In the design of new drugs, the development of hybrid molecules through the combination of different scaffolds in one frame may lead to compounds with interesting biological profiles.…”
Section: Introductionmentioning
confidence: 99%